The Moderating Influence of Cultural Tightness on the International Diversification–Firm Performance Relationship: A Meta-analysis - Schüler, Jens (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
The relationship between international diversification (ID) and firm performance (FP) is among the best researched topics in international business. However, the findings on the role of firms’ home-country culture remain mixed, leading to repeated calls for broader cultural perspectives. We introduce the construct of cultural tightness–looseness and advance the conversation on the role of the tightness of a firm’s cultural origin. Drawing on 490 primary studies, we provide meta-analytic evidence that cultural tightness negatively moderates the ID–FP relationship.